Varieties of monetary experience - Meiselman, David (Chicago : University of Chicago Press, 1970)
This book contains a comparative analysis of monetary phenomena of countries like Chile, Argentina, Japan, Canada, South Korea and Brazil, from various scholars.
The workshop was organized by Economic Research Studies of the Economics Research Center of the University of Chicago.
Includes bibliographical references and index.
usc 13/9/17
Loans
Keywords: Money; Quantity theory of money; Monetary policy